IDENTIFIKASI KARAKTER TOLERANSI CEKAMAN KEKERINGAN BERDASARKAN RESPONS PERTUMBUHAN DAN HASIL GENOTIPE JAGUNG - Roy Efendi; Muhammad Azrai (Widyariset, 2010)
The objectives of this experiment were to study (a) response of maize genotypes drought stress during anthesis up to grain filling or maturity stages and (b) determine characters as drought tolerance indicators. Factorial randomize complete block design this experiment was used with two factors. The first factor was drought tolerance and sensitive genotypes and the second factor was periods of drought stress consisted of three condition: (i) drought at anthesis up to grain filling stages, (ii) drought at anthesis up to maturity stages, and (iii) optimum condition.The results of research showed that tolerance genotypes had the abilities to maintain shoot growth (plant height and shoot dry weight) and suppress leaf damage under drought condition. The abilities of drought tolerant were supported by heavy root dry weight while resulted the extend of root absorbing more water. The ability of maize genotypes in keeping shoot growth, suppressing transpiration due to lower leaf stomata density and higher water use efficiency is an important factors in suppressing yield loss in drought condition. The sensitive genotypes wasnot had these abilities since it had low root dry weight, therefore, the root extension was not supported for absorbing adequate amount of water for shoot growth (shoot dry weight and plant height) and increasing the intensityof damage leaf under drought condition was high. Besides, the sensitive genotype had higher leaf stomata density and lower level of water use efficiency which caused the increasing yield decrease (grain wieght/plant) compare to tolerance genotypes, more over, in longer drought period of theirs genotypes were not filled.